Evolutionary Stability Analysis of the Coal Mine Safety Management System Governed by Delay and Impulsive Differential Equations - Li Bai; Xinhua Wang; Rongwu Lu; Hao Yu; Dan Li (Complexity)
Control of unsafe behaviors has always been a difficult point in Coal Mine Safety Management (CMSM). To study the regular pattern of behavior propagations in CMSM, a series of evolutionary dynamical system models are established by the delay and impulsive differential equations (DIDEs). The threshold constraints (TCs) and impulse responses in the models can accurately correspond to the actual inspection and supervision measures in safety management. Through the simulation analysis and comparison of the system stability, it can be concluded that some proper settings of the TCs and impulse responses bring satisfactory evolutionary stability. Based on the main results of this study, we put forward some decision-making suggestions on the control points and control strategies of unsafe behaviors in safety management.